Pedagogical And Psychological Characteristics of The Development of Writing Skills in Weak Students - Shakhnoza Torakulova (Open Academia, 2024)
This article covers the information based on the scientific research of foreign and local scientists on the development of intellectual skills of students with mental retardation.
Keywords: Pedagogy; psychology; writing; literacy